Ocular trauma from land mines among soldiers treated at a University Hospital in Medellín, Colombia - Moreno, Liliana; Velasquez, Luis Fernando; Restrepo, Carlos Alberto; Paulo, Jose David; Donado, Jorge Hernando; Muñoz, Marta Lucía; Aristizabal, John Jairo (Colombia Medica, 2013)
Introduction: Currently ocular combat injuries are complex and associated with poor visual outcomes. Our objective is to characterize the military population that suffer land mine combat ocular trauma in Colombia and indentify the type of wound, treatment and visual outcomes. Methods: Retrospectively review of medical history of soldiers evaluated in Pablo Tobon Uribe Hospital, whom had land mine trauma during January of 2004 and December 2012. Results: 635 soldiers had land mine trauma, 153 of them had ocular trauma (226 eyes). Open ocular trauma was observed in 29.6%. The Ocular Trauma Score was calculated in 183 eyes, the initial visual acuity was not possible to be reported in the rest of them; the 45% of the eyes were classified in category 3. Three patients had no light perception in both eyes. 97.3% of the eyes received medical treatment and 49.1% had surgery also. Primary evisceration was made in 5.8% and enucleation in 1.8%. Intraocular foreign body was observed by ultrasonography in 11.1% and in 5.8% by orbital tomography. Eleven patients were legally blind at discharge. Conclusions: The ocular trauma related to a landmine is highly destructive at an ocular level. The treatments associated with better visual outcomes are primary closure of globe and systemic antibiotics; although the characteristics of the wound itself are the main prognostic factor. The Ocular trauma score is a useful tool for determining visual outcome in combat ocular trauma.